Ethnomathematics Exploration on 7 Bidadari Waterfall Tourism in Rowosari Village - Alfiansyah Baskoro; Dimas Anditha Cahyo Sujiwo; Nur Hidayatin (International Journal of Trends in Mathematics Education Research, 2025)
Ethnomathematics is a study that investigates mathematical concepts in a cultural context, applied to the design and objects of cultural diversity, including tourist attractions. This study explores the concept of ethnomathematics at the 7 Bidadari Waterfall tourist attraction located in Rowosari village, focusing on the interaction between mathematics and the surrounding culture. The findings of this study highlight that the 7 Bidadari Waterfall tourist attraction is not only a tourist destination but also reflects the mathematical values inherent in the activities of the local community. The main focus of this study is to explore the mathematical concepts contained in the design of the 7 Bidadari Waterfall tourist attraction, with an emphasis on geometric patterns and mathematical proportions seen in the decoration of the tourist attraction and the surrounding natural features. The research method used is a qualitative one with an ethnographic approach, where observation and documentation are used as data collection tools. The data analysis process is carried out through several steps, namely, reduction, presentation, and interpretation. The results of the study indicate that the 7 Bidadari Waterfall, in addition to functioning as a vacation spot, also reflects mathematical values that are useful for learning. This research offers fresh viewpoints about the relationship between mathematics, culture, and architecture at the 7 Bidadari Waterfall.